Numerical Simulation and Experimental Analysis of The Equal Channel Angular Pressing of Pure Titanium - Quang, Pham; Nghiep, Do Minh (Korean Journal of Metals and Materials, 2016)
The plastic deformation behavior of pure Ti during equal channel angular pressing (ECAP) is simulated using the three-dimension finite volume method and is experimentally investigated. The calculated effective strain and effective stress distributions and histories are analyzed to understand the local and global deformation characteristics. The predicted plastic deformation behavior of the Ti workpiece during the ECAP process was compared with the theoretical total strain for every pass at RAM speed v of 10 mm/s and at constant temperature of 400 ℃. The simulated strain and stress distributions are homogenous in the central region of the ECAP processed Ti. The experimental ECAP performed with four, eight, and twelve passes at 400 ℃ results in refined grain sizes of approximately 5-10 μm, 0.4-0.5 μm and 0.1-0.2 μm, respectively. KCI Citation Count: 0